كشف الإشارات المستقطبة جزئياً بوجود التشويش المستقطب جزئياً - احمد علي; يونس معين (Latakia University Journal -Engineering Sciences Series, 2019)
تم في البحث التالي تقديم خوارزميات المعالجة لمركبات الحقل الفراغية للإشارة والتشويش المستقطبان جزئياً واللتان يخضعان لقانون التوزيع الغوصي الإحصائي بحيث نتمكن من تحديد المعطيات المناسبة لأفضل احتمال للكشف مع وجود قيم طورية مختلفة للإشارة والتشويش. تقيم فعالية الخوارزميات المقترحة تم من خلال تحديد أثر عوامل مختلفة في عملية الكشف كاستطاعة المركبات الفراغية للإشارة والتشويش وأثر ثوابت الحقل في فعالية الكشف. البحث يشكل اساساً في تصميم كواشف مثالية ويساعد في استنتاج عتبة الإشارة وعدد مرات المراقبة اللازمة للتصميم. This research presents a processing algorithm of vacuum field to the signals and partial polarization confusion, which submits to the Statistical Gousen Distribution. The aim is define the suitable circumstances for the best possibility of detection during different phasing values of signals and confusion. The evaluation of suggested algorithm efficiency had been completed through definition of the effect of different factors on the detection operation like the power of the vacuum compounds of signals and confusion and definition of field constants on detection evaluation. This research forms a basis in designing perfect decoders and supports in concluding the signal threshold and number of the observations necessary for the design.